The influence of the glass transition temperature (T g) of polymers on early OPC hydration: a complete study of the heat flow, phase evolution, and pore solution chemistry - Jansen, Daniel; Lu, Z.; Kong, X. M.; Pakusch, J.; Jahns, E.; Deschner, F.; Schmidtke, Ch (Materials and Structures, 2019)
The impact of two different dialyzed styrene-acrylate polymer dispersions on the early hydration of OPC was studied. The polymer particles of both dispersions show a similar particle size distribution and high charge due to carboxylic groups on the surface of the particles. Both dispersions also show similar adsorption behavior. The hydration of the OPC was studied at a polymer concentration below the initial adsorption in order to evaluate possible reasons for the interaction of the polymer particles with cement hydration. It can be shown that the polymer particle with the lower glass transition temperature Tg shows a stronger impact on cement hydration, which cannot be explained by any influence on the pore solution composition or the initial dissolution of cement phases. Hence, the adsorption mechanism seems to be the most likely cause of the interaction of the polymers with hydrating cement.
CRIS-Team Scopus Importer:2019-12-24
Keywords: Cement hydration; Glass transition temperature; Polymers; Pore solution; Retardation